Bibliographical services throughout the world. - Unesco (Paris Unesco, 1955)
Quinquennial, 1960-1964-1975-1979 Annual Quadrennial, 1953-1956 1950-59
Issued also in French: Services bibliographiques dans le monde.
Report year ends Aug. 31 for 1951-52, 1952-53-1953-54 vols.
Keywords: Bibliographical services -- Periodicals